PENDAMPINGAN UMKM “MASE RAHMAN” MENUJU PENERAPAN CPPOB DAN IZIN EDAR PRODUK PANGAN OLAHAN DI KOTAWARINGIN BARAT - Hasdin, Hasdin; Apriyasni Melati,; Ria Septiani, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the processed food sector play a strategic role in the local economy; however, they continue to face challenges related to the implementation of food safety standards and compliance with business legality requirements. Mase Rahman, a micro-scale processed food enterprise, had not systematically implemented Good Manufacturing Practices for Processed Food (GMP/CPPOB) and did not possess a product distribution permit prior to the assistance program. This community service activity aimed to enhance the capacity of micro, small, and medium enterprises in implementing CPPOB and preparing for compliance with processed food licensing requirements. The methods employed included initial observation, CPPOB education and training, on-site technical assistance, preparation of CPPOB supporting documents, as well as evaluation and monitoring of implementation. The assistance was carried out gradually and continuously, tailored to the actual conditions of the partner enterprise. The results demonstrated an improvement in the business owner's understanding and awareness of food safety, enhancements in production facilities and processes, and the establishment of standard operating procedures and sanitation documentation. Furthermore, the assistance successfully improved the administrative readiness of the MSME, leading to the issuance of a BPOM certificate and an official product distribution permit. This activity confirms that practical and sustainable CPPOB assistance is effective in improving product quality, food safety, and legal compliance of micro-scale processed food enterprises. This assistance model has the potential to be replicated for similar micro-enterprises to strengthen competitiveness and ensure business sustainability